Hummingbirds - Borgert-Spaniol, Megan, 1989- (Blastoff! readers. Backyard wildlife., 2014)
"Developed by literacy experts for students in kindergarten through grade three, this book introduces Hummingbirds to young readers through leveled text and related photos"--